2015
DOI: 10.1016/j.jhsa.2015.08.009
|View full text |Cite
|
Sign up to set email alerts
|

Pyrocarbon Proximal Interphalangeal Joint Arthroplasty: Minimum Five-Year Follow-Up

Abstract: Therapeutic IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
47
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(49 citation statements)
references
References 34 publications
2
47
0
Order By: Relevance
“…1921 Although the volar approach to PIP joint arthroplasty was suggested recently, 22 the dorsal approach to PIP joint was commonly used for these surface replacement arthroplasties. 23,24 Various surface replacement arthroplasty designs were introduced that have a concept of anatomical reconstruction unlike silicone spacer, in which the implant acts as an internal splint that requires the soft tissues to rebalance. 25 However, there is no comparative study for outcomes of silicone spacer and nonconstrained surface replacement PIP arthroplasty with different approaches.…”
Section: Introductionmentioning
confidence: 99%
“…1921 Although the volar approach to PIP joint arthroplasty was suggested recently, 22 the dorsal approach to PIP joint was commonly used for these surface replacement arthroplasties. 23,24 Various surface replacement arthroplasty designs were introduced that have a concept of anatomical reconstruction unlike silicone spacer, in which the implant acts as an internal splint that requires the soft tissues to rebalance. 25 However, there is no comparative study for outcomes of silicone spacer and nonconstrained surface replacement PIP arthroplasty with different approaches.…”
Section: Introductionmentioning
confidence: 99%
“…Many of these studies use a dorsal tendon splitting, or reflecting, approach, with 1 small series describing outcomes using a volar approach. 1,4,7,8,10,13,14,[16][17][18][19][20][21] Patients included in these series often reported substantial pain relief and improvement in function; however, poor outcomes have also been reported. 20 The most commonly reported complication in these studies was joint stiffness which frequently required treatment with an extensor tendon tenolysis and excision of dorsal osteophytes.…”
Section: Introductionmentioning
confidence: 99%
“…20 The most commonly reported complication in these studies was joint stiffness which frequently required treatment with an extensor tendon tenolysis and excision of dorsal osteophytes. 1,4,7,8,10,13,14,[16][17][18][19][20][21] Reoperation rates ranged widely, from 5% to 58%, and time to reoperation ranged from 7 months to 24 months when reported. 1,4,7,8,10,13,14,16,17,19,21 A dorsal approach to the PIP joint does provide some advantages, particularly improved visualization of the articular 662020H ANXXX10.1177/1558944716662020HANDTrumble and Heaton research-article2016 1 Bellevue Hand Institute, WA, USA 2 Pacific Northwest University of Health Sciences, Yakima, WA, USA surface.…”
Section: Introductionmentioning
confidence: 99%
“…All these stress-strain results reveal mainly a potential risk of fatigue failure of support cancellous-bone due to cyclic loads, which is enhanced by the magnitude of joint loads as well as by the number of load cycles. This potential risk may be related with several clinical mid-long term outcomes that evidence the ongoing migration, dislocation, tilt and potential failure Ascension PyroCarbon prosthesis (Chan et al, 2013;Ceruso et al, 2017;Dickson et al, 2015;Reissner et al, 2014;Sweets and Stern, 2011). Limiting the magnitude of index finger forces after arthroplasty can contribute positively to reduce the overload effect in the cancellous-bone adjacent to the pyrocarbon implant reducing the risk of fatigue failure of the support bone.…”
Section: Discussionmentioning
confidence: 99%
“…Most of retrospective clinical studies found that pyrocarbon PIP joint arthroplasty provided patients with excellent pain relief overall and maintained their preoperative PIP joint motion; however, overall implant complications has been very variable, with some good outcomes at short-medium-term follow-up (Branam et al, 2007;Bravo et al, 2007;Chung et al, 2009;Desai et al, 2014;Mashhadi et al, 2012;McGuire et al, 2012;Watts et al, 2012) and some bad outcomes at medium-longer-term follow-up (Chan et al, 2013;Daecke et al, 2012;Dickson et al, 2015;Hutt et al, 2012;Ono et al, 2012;Reissner et al, 2014;Squitieri and Chung, 2008;Sweets and Stern, 2011). Implant loosening with migration, dislocation and implant fracture were the main reported clinical complications (Chan et al, 2013;Ceruso et al, 2017;Dickson et al, 2015;Sweets and Stern, 2011;Reissner et al, 2014). Studies on the structural biomechanics of PIP pyrolytic carbon arthroplasty are very limited.…”
Section: Introductionmentioning
confidence: 99%